(untitled) (Research, Society and Development, 2021)
This study aimed to determine the seroprevalence of leptospirosis in racehorses hosted at the Jockey Club of Pelotas (JCP) and the risk factors related to this disease. Eighty-four thoroughbred horses were included in this study. The animals were submitted to physical exams and were bled to obtain serum samples. Microscopic agglutination test (MAT) was performed for the following L. interrogans serovars: Australis, Autumnalis, Batavie, Bratislava, Copenhageni, Grippothyphosa, Hardjoprajitno, Icterohaemorrhagiae, Pomona, Pyrogenes and Patoc, being considered reagent when agglutination was ≥ 1:100. Subsequently, a single interviewer applied an epidemiological questionnaire to those responsible for the horses to determine the presence of risk factors for leptospirosis at the JCP. Among the 84 horses, only nine (10.7%) had titers for L. interrogans. Titers ranged between 1:100 and 1:400, and three horses had titers for more than one serovar. The serovars identified in this study were Canicola (33.3%), Grippotyphose (33.3%), Icterohaemorrhagiae (22.2%), Australis (22.2%), Pyrogenes (11.1%), Bratislava (11,1%), Copenhageni (11.1%), Autumnalis (11.1%) and Hardjoprajitno (11.1%). There was no association between the results of the serological test and the data obtained through the epidemiological questionnaire (p > 0.05). This study demonstrated that the seroprevalence for L. interrogans in horses hosted at the JCP is low. Epidemiological studies in other racecourses to determine risk factors that are associated with L. interrogans infection in racehorses.